On the estimates of the rate of propagation of perturbations in quasilinear divergent degenerated parabolic equations of the high order - Shyshkov, A. E. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A method is given for obtaining integral growth lemmas for solutions of boundary problems for a large class of quasilinear evolution equations. As a possible application a sharp estimate is obtained of the dependence of the support of a solution of a mixed problem and a Cauchy problem for a quasilinear divergent parabolic equation on time.